2021
DOI: 10.1101/2021.05.18.444740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The FusX TALE Base Editor (FusXTBE) for rapid mitochondrial DNA programming of human cells in vitro and zebrafish disease models in vivo

Abstract: Functional analyses of mitochondria have been hampered by few effective approaches to manipulate mtDNA and a lack of existing animal models. Recently a TALE-derived base editor was shown to induce C-to-T (or G-to-A) sequence changes in mtDNA. We report here the FusX TALE Base Editor (FusXTBE) to facilitate broad-based access to TALE mitochondrial base editing technology. TALE Writer is a de novo in silico design tool to map potential mtDNA base editing sites. FusXTBE was demonstrated to function with comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 30 publications
(61 reference statements)
0
37
0
Order By: Relevance
“…Mutations in MT-Nd5 (ND5) generated by delivering DdCBE mRNA in mouse embryos were maintained throughout development and successfully transmitted to offspring (F1) 105 . Furthermore, one published study 106 and a pre-print 107 reported DdCBE-mediated mtDNA base editing in zebrafish embryos.…”
Section: Mtdna Modification With Base Editorsmentioning
confidence: 99%
“…Mutations in MT-Nd5 (ND5) generated by delivering DdCBE mRNA in mouse embryos were maintained throughout development and successfully transmitted to offspring (F1) 105 . Furthermore, one published study 106 and a pre-print 107 reported DdCBE-mediated mtDNA base editing in zebrafish embryos.…”
Section: Mtdna Modification With Base Editorsmentioning
confidence: 99%
“…Indeed, the mycotoxins covered here include aflatoxins (aflatoxins B1, B2, G1, G2, M1, M2) [ 2 , 39 ], ochratoxin A [ 40 , 41 ], deoxynivalenol (DON) [ 42 ], fumonisins (fumonisins B1, B2, B3, B4) [ 43 , 44 , 45 , 46 ], zearalenone (ZEA), also known as F-2 mycotoxin [ 3 , 47 ], patulin, citrinin [ 38 , 42 ], ergot alkaloids [ 25 ], and T-2, which is a trichothecene mycotoxin [ 48 , 49 , 50 ]. Other mycotoxins captured in Table 2 include diacetoxyscirpenol (DAS) or 4,15-diacetoxyscirpenol (DAS), also referred to as anguidine [ 51 , 52 , 53 ], fusarenon X (FusX) [ 54 , 55 , 56 ], and nivalenol (NIV) [ 57 , 58 ]. In subsequent sections, we discuss these mycotoxins in greater detail with respect to their mechanisms of action, as well as the ailments they cause.…”
Section: Mycotoxins: Their Toxicological Mechanisms and Associated He...mentioning
confidence: 99%
“…Fusarenon X (FusX) is a trichothecene capable of causing cytotoxicity, carcinogenicity, and immunosuppressive response in animal models and possibly in humans. It has been shown to be toxic to several types of cells, including murine thymocytes, gastric epithelial cells, and lymphocytes, along with a high toxicity to human hepatoblastoma cells [ 54 , 56 , 166 ]. In vitro and in vivo, FusX initiates apoptosis in mouse thymocytes, which may be hypothetically applicable to humans [ 53 , 55 ].…”
Section: Mycotoxins: Their Toxicological Mechanisms and Associated He...mentioning
confidence: 99%
See 1 more Smart Citation
“…This tool is designed to be easily modified to work in diverse applications where editing of mitochondrial DNA is desired. For complete details on the use and execution of this protocol, please refer to Sabharwal et al. (2021) and Ma et al.…”
mentioning
confidence: 99%